MITIGASI KECELAKAAN KERJA DI AREA WORKSHOP PT DECE MENGGUNAKAN METODE HIRADC DENGAN PENDEKATAN FTA - Kurnia Taufan Febriyanto, (2020)
The number of emerging industries proves that the industry sector is one of the fields of interest. Job eligibility is not only judged by the amount of wages / salaries, but the level of comfort and security provided by the company becomes a consideration, especially in the industrial sector. Occupational safety and health (K3) is an effort made to provide protection and security as well as the comfort of every worker in performing work. PT. DECE is a manufacturing industry with products in the form of industrial pumps. Therefore, it is necessary to have proper safety standards obtained by workers to feel safe and comfortable at work. The HIRA (Hazard Identification and Risk Assessment) method was chosen to evaluate the application of OHS at PT. DECE through the FTA (Fault Tree Analysis) approach. Based on the assessment of potential hazards using the HIRA method there are 4 potential occupational hazards found with 1 extreme risk hazard and 3 high risk hazard. Risk findings including facilities and high-risk activities were evaluated by fault tree analysis with top event collisions with workpieces and machinery, webbing broken links, misalignment of remote crane laying, and electric shock problems. Then mitigation measures are taken in the form of eliminating unsafe conditions and unsafe actions, conducting K3 training for employees and breafing regarding safety first before starting work, as well as paying attention and understanding the applicable SOP.